How family influence, socioemotional wealth, and competitive conditions shape new technology adoption - Souder, David; Zaheer, Akbar; Sapienza, Harry; Ranucci, Rebecca (Strategic Management Journal, 2017)
Research summary : In family businesses, investment decisions often involve both socioemotional wealth and economic considerations. Focusing on new technology adoption, we argue that multiple dimensions of socioemotional wealth contribute to complex effects within different types of family firms—depending on the level of family control—as well as in contrast to non‐family firms. Results based on cable TV operators from 1983 to 1987 confirm that family ownership correlates negatively with technology adoption, especially when family owners hold a minority rather than majority position. We also show contingencies based on performance improvements and competitive threats. Our arguments contribute new insights about the tensions between economic and socioemotional factors within minority family ownership that are absent from non‐family firms and more pronounced than in majority family firms. Managerial summary : We find evidence of greater reluctance toward new technology adoption among firms with minority family influence than majority family influence. This suggests that goals related to socioemotional wealth only partly explain the cautious decision‐making observed in family firms, with further caution arising from conflicting priorities between family and non‐family owners. Recent performance improvements help offset the reluctance to adopt new technology, albeit to a lesser degree among firms with minority family ownership. High levels of competitive threats also offset the reduction in new technology adoption, and contrary to expectations, to a greater extent among minority family firms . Copyright © 2016 John Wiley & Sons, Ltd.